The Meaning & Significance of Tribalism - Khan, Imran; Seeneen, Kiran (sourcecoder, 2024)
Tribalism is the name of unconditional love and affection for the values and attitudes of one’s family or one’s tribe, which does not allow them to disappear in any way. However, some negative attitudes are kept in mind along with positive values in tribalism but still tribes feel proud of it and it becomes a source of their identity. Even today, the world is a collection of many tribes that have their own sacred traditions and rituals and they look at them very seriously. The head gives them recognition and importance and attention is paid to their antiquity. It should also be mentioned that due to some negative attitudes, the tribes are facing many issues and problems, that are behind the full hands of the local administrative authority because the tribes cannot move from the dark to the light and they are facing deprivation. It should also be remembered that there are still tribes in the world. How Pashtuns are recognized by this reference and have become part of modern world.